Light to moderate intake of alcohol, drinking patterns, and risk of cancer: results from two prospective US cohort studies. (18th August 2015) - Cao, Yin; Willett, Walter C; Rimm, Eric B; Stampfer, Meir J; Giovannucci, Edward L
Abstract : Objectives To quantify risk of overall cancer across all levels of alcohol consumption among women and men separately, with a focus on light to moderate drinking and never smokers; and assess the influence of drinking patterns on overall cancer risk. Design Two prospective cohort studies. Setting Health professionals in the United States. Participants 88 084 women and 47 881 men participating in the Nurses' Health Study (from 1980) and Health Professionals Follow-up Study (from 1986), followed until 2010. Main outcomes and measures Relative risks of cancer. Results 19 269 and 7571 (excluding non-advanced prostate cancers) incident cancers were documented among women and men, respectively, over 3 144 853 person years. Compared with non-drinkers, light to moderate drinkers had relative risks of total cancer of 1.02 (95% confidence interval 0.98 to 1.06) and 1.04 (1.00 to 1.09; Ptrend =0.12) for alcohol intake of 0.1-4.9 and 5-14.9 g/day among women, respectively. Corresponding values for men were 1.03 (0.96 to 1.11), 1.05 (0.97 to 1.12), and 1.06 (0.98 to 1.15; Ptrend =0.31) for alcohol intake of 0.1-4.9, 5-14.9, and 15-29.9 g/day, respectively. Associations for light to moderate drinking and total cancer were similar among ever or never smokers, although alcohol consumption above moderate levels (in particular ≥30 g/day) was more strongly associated with risk of total cancer among ever smokers than never smokers. For a priori defined alcohol related cancers in men, risk was not appreciably increased for light and moderate drinkers who never smoked (Ptrend =0.18). However, for women, even an alcohol consumption of 5-14.9 g/day was associated with increased risk of alcohol related cancer (relative risk 1.13 (95% confidence interval 1.06 to 1.20)), driven by breast cancer. More frequent and heavy episodic drinking was not further associated with risk of total cancer after adjusting for total alcohol intake. Conclusion Light to moderate drinking is associated with minimally increased risk of overall cancer. For men who have never smoked, risk of alcohol related cancers is not appreciably increased for light and moderate drinking (up to two drinks per day). However, for women who have never smoked, risk of alcohol related cancers (mainly breast cancer) increases even within the range of up to one alcoholic drink a day.